POSE STRATEGY AS A MEDIA FOR TOURISM DESTINATION - Setiawati, Rahmi (Journal of Indonesian Tourism and Policy Studies, 2020)
Batu City is one of the tourist cities in Indonesia that has many tourist destinations, so a POSE strategy is needed to promote Batu City tourist destinations. The management of promotional activities is carried out by stakeholders and the Batu City Tourism Office as direct actors who develop and promote tourist destinations. The concepts used are tourism, strategy, marketing, and promotional media. The method used in this research is qualitative, supported by data sources from observations, interviews and literature study. The results of this study indicate that the POSE strategy is carried out through P (paid media), namely, Agropolitan TV (Local TV), Magazines and billboards, O (own media) through the Official Website (www.batukota.go.id), among applications city, calendar of events, while S (social media) via TikTok, YouTube, blog and Instagram. and E (Endoser), namely Tourism Ambassador. The name of the Tourism Ambassador used is Kangmas Nimas Batu City. POSE is carried out in order to promote tourist destinations in Batu City, each party always collaborates and integrates to achieve the same goals, namely to make Batu City a tourism city that can bring in domestic tourists and also foreign tourists. Suggestions for the future always use a new promotional media strategy in order to achieve the goal of developing Batu City tourism in a sustainable manner.